Salt Stress Represses Soybean Seed Germination by Negatively Regulating GA Biosynthesis While Positively Mediating ABA Biosynthesis - Shu, Kai; Qi, Ying; Chen, Feng; Meng, Yongjie; Luo, Xiaofeng; Shuai, Haiwei; Zhou, Wenguan; Ding, Jun; Du, Junbo; Liu, Jiang; Yang, Feng; Wang, Qiang; et al. (Frontiers in Plant Science, 2017)
Soybean is an important and staple oilseed crop worldwide. Salinity stress has adverse effects on soybean development periods, especially on seed germination and post-germinative growth. Improving seed germination and emergence will have positive effects under salt stress conditions on agricultural production. Here we report that NaCl delays soybean seed germination by negatively regulating gibberellin (GA) while positively mediating abscisic acid (ABA) biogenesis, which leads to a decrease in the GA/ABA ratio. This study suggests that fluridone (FLUN), an ABA biogenesis inhibitor, might be a potential plant growth regulator that can promote soybean seed germination under saline stress. Different soybean cultivars, which possessed distinct genetic backgrounds, showed a similar repressed phenotype during seed germination under exogenous NaCl application. Biochemical analysis revealed that NaCl treatment led to high MDA (malondialdehyde) level during germination and the post-germinative growth stages. Furthermore, catalase, superoxide dismutase, and peroxidase activities also changed after NaCl treatment. Subsequent quantitative Real-Time Polymerase Chain Reaction analysis showed that the transcription levels of ABA and GA biogenesis and signaling genes were altered after NaCl treatment. In line with this, phytohormone measurement also revealed that NaCl considerably down-regulated active GA1, GA3, and GA4 levels, whereas the ABA content was up-regulated; and therefore ratios, such as GA1/ABA, GA3/ABA, and GA4/ABA, are decreased. Consistent with the hormonal quantification, FLUN partially rescued the delayed-germination phenotype caused by NaCl-treatment. Altogether, these results demonstrate that NaCl stress inhibits soybean seed germination by decreasing the GA/ABA ratio, and that FLUN might be a potential plant growth regulator that could promote soybean seed germination under salinity stress.